Efektivitas Kinerja Pelayanan Surat Ijin Mengemudi Pada Satuan Lalu Lintas Kepolisian Resor Kota Manado - Baghi, Yuliana Yulita; Goni, John Hein (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract. This study aimed to assess the performance of a driver's license services at the Office of the City Police Force Traffic Resort Manado (Manado Police Satlantas). The focus of research regarding police professionalism, work ethic and leadership. The research method used is qualitative, so it does not use statistical data analysis. Data collection was obtained through in-depth interviews of informants to 15 people consisting of 10 applicants driving license and 5 police officers in the service of a driver's license. The results showed that the performance of the service has been excellent driving license that the applicant satisfied. This is because of the behavior of a professional working of police officers and supported the spirit of the work or the work ethic of the maximum. In addition, the lack of leadership that is conducive to making police officers performing services effective driving license. However, there are still complaints of the applicant's driver's license on time and queue length as the number of police on duty are lacking. Need additional officers, when recess was a replacement officer to prevent the happening of a long queue. Also need to limit the number of driver's license applicants every day, as well as more advanced for the time of registration of the applicant does not have to wait too long to get a driver's license.Key words: Professionalism, Behavior, Leadership